Unilateral biportal endoscopic spine surgery: A game changer in spine care - Dash, Atmaranjan; Dhawali, Vaibhav S.; Patil, Mandar (Journal of Neurosurgery Academy, 2025)
Unilateral Biportal Endoscopic spine surgery is a minimally invasive technique using two portals for visualization and instrumentation. It offers enhanced precision, reduced tissue disruption, and faster recovery. This paper reviews its applications, advantages, and evolving role in spine care, including recent advancements in robotics and augmented reality.